Task-Based Language Teaching in Developing Marine and Fisheries Students’ Speaking Skill (A Study in SUPM Negeri Ladong, Aceh) - Ikhwan Wahidin (ELT Worldwide: Journal of English Language Teaching, 2016)
The objective of the research were (1) To obtain an empirical evidence for the lack of knowledge we have right now about how TBLT is used in developing Marine and Fisheries students’ English speaking proficiency. (2) To find out students’ perceptions on the implementation of TBLT whether learning with TBLT is helpful to understand the lesson or not. The research method was quasi experimental. This research assigned two groups, experimental and control group. Each group consisted of 25 students. The sample was chosen by applying purposive sampling technique. The data obtained through the test were analyzed by using descriptive and inferential statistic. Then the data on the students’ perception in learning speaking by using TBLT approach was collected through questionnaire. The research result showed that there was a positive development on the students’ speaking achievement. It was proved by the mean score of the students’ posttest in experimental group that showed 67.64 while the mean score of the students’ posttest in control group was 56.08. It means that there was a positive development in experimental group. With those several benefits, TBLT ensures that students have a high positive perception. It was proved with majority students’ perception which is 76%. It was classified as high and it can be concluded that TBLT is helpful approach. Key word : Task-Based Language Teaching, Marine and Fisheries' Speaking Skill.